Manganese increases high mannose glycoform on monoclonal antibody expressed in cho when glucose is absent or limiting: implications for use of alternate sugars - Surve, Tanaya; Gadgil, Mugdha (Biotechnology Progress, 2015)
Alternate sugars such as galactose and fructose are metabolized at a slower rate than glucose and result in lower accumulation of lactate. While low lactate accumulation is desirable, we report that complete substitution of glucose with these sugars results in an increase in M5 high mannose glycans. Surprisingly, this increase is much higher when the culture is supplemented with manganese: for example, when cells are cultured with galactose, M5 high mannose glycan content increased from 5% at 1 nM Mn2+ in the basal medium to 32% with 16 mu M Mn2+ supplementation. When galactose is supplemented with glucose maintained at low concentrations, a small reduction in high mannose glycans is seen. In control cultures with glucose, the high mannose content was however <2% in this range of Mn2+ concentration. By varying Mn2+ and glucose supplementation levels, with or without galactose, we systematically demonstrate that Mn2+ concentration and glucose availability, together, significantly affect the high mannose glycan content. To our knowledge, this is the first report that shows that the effect of Mn2+ on high mannose glycan content depends on glucose availability. At each Mn2+ supplementation level evaluated, galactosylation percentages were highest for cultures where galactose was supplemented with glucose at non-limiting concentration. (c) 2014 American Institute of Chemical Engineers Biotechnol. Prog., 31:460-467, 2015
Keywords: CHO; fructose; galactose; glucose; glycosylation; high-mannose glycan; manganese

Cell culture processes for biopharmaceutical manufacturing - Gadgil, Mugdha (Current Science, 2017)
Recombinant proteins manufactured using animal cell culture processes comprise a significant fraction of biopharmaceuticals. With the expiry of patents on this class of therapeutics, there is also a significant interest in manufacture of biosimilar versions of such therapeutics. This article provides a birds-eye view of upstream process development for animal cell culture processes, with a focus on advances pertinent to the development of processes for biosimilars.
Keywords: Biopharmaceutical; Cell line development; CHO; glycosylation; monoclonal antibody

Zinc supplementation decreases galactosylation of recombinant IgG in CHO cells - Prabhu, Anuja (Applied Microbiology and Biotechnology, 2018)
Trace element composition of culture medium can be altered to modulate glycoform of recombinant glycoproteins. In this study, we show that Zn2+ supplementation at or above 100 μM decreases galactosylation of recombinant IgG expressed in Chinese Hamster Ovary cells. This decrease in galactosylation is not due to reduced galactosyltransferase expression. This effect persists upon supplementation of galactose and uridine to the culture, indicating that it may not be due to reduced UDP-Gal availability. Measurements of galactosyltransferase activity in the cell lysate show that activity decreases with increasing Zn2+/Mn2+ ratio. This suggests that one possible explanation of the effect of Zn2+ may be reduced intracellular galactosyltransferase activity due to increase in Zn2+/Mn2+ ratio. Consistent with this, the decrease in galactosylation of IgG could be reversed by supplementation of Mn2+ (a cofactor of galactosyltransferase) which increases intracellular Mn2+ content. Measurement of total intracellular Zn2+ content, however, indicates no significant upregulation of total intracellular Zn2+ content and no significant downregulation of intracellular Mn2+ content with Zn2+ supplementation. One possible explanation could be that cellular detoxification response to higher extracellular Zn2+ concentration might lead to changes in intracellular distribution of Mn2+. In this case, Zn2+ supplementation would be expected to interfere with other known effects of Mn2+. Indeed, the previously reported increase in high mannose glycans upon Mn2+ supplementation in the absence of glucose is reversed by Zn2+ supplementation. This study also suggests the use of Mn2+ supplementation as a strategy to overcome the effect of lot-to-lot variability in trace element concentrations on galactosylation.
Keywords: CHO cells; glycosylation; manganese; Trace metals; zinc

Trace metals in cellular metabolism and their impact on recombinant protein production - Prabhu, Anuja; Gadgil, Mugdha (Process Biochemistry, 2021)
Replacement of serum and increasing use of chemically defined media demands optimisation of trace metal components for biomanufacturing applications. Trace metal availability can impact culture performance, productivity and product quality. Several trace metals are cofactors of metabolic and other enzymes, and thus their availability regulates cellular metabolism. Additionally, they can also affect the availability of other trace metals and stability of some medium components. Such factors also need to be considered while formulating trace metal concentrations in the culture medium. Due to their very low concentrations, these components are susceptible to substantial variability arising from contaminants from other raw material and leaching from process equipment and can contribute to process variability. Understanding the role and impact of trace metals will help develop strategies to achieve targeted process parameters and increase process robustness vis-`a-vis any lot-to-lot variability in trace metal concentration in culture medium. This review describes the role of trace metals, particularly manganese, copper and zinc, in central carbon metabolism to aid in understanding the basis of metal-mediated effects on culture performance and provides a comprehensive review of the reported impact of trace metals on CHO cell culture performance and recombinant protein quality.
Keywords: Chinese hamster ovary cells; glycosylation; Medium formulation; Process variability; Product quality; Recombinant proteins; Trace metals

Engineering nucleotide sugar synthesis pathways for independent and simultaneous modulation of N-glycan galactosylation and fucosylation in CHO cells - Prabhu, Anuja; Shanmugam, Dhanasekaran; Gadgil, Mugdha (Metabolic Engineering, 2022)
Glycosylation of recombinant therapeutics like monoclonal antibodies (mAbs) is a critical quality attribute. N-glycans in mAbs are known to affect various effector functions, and thereby therapeutic use of such glycoproteins can depend on a particular glycoform profile to achieve desired efficacy. However, there are currently limited options for modulating the glycoform profile, which depend mainly on over-expression or knock-out of glyco-syltransferase enzymes that can introduce or eliminate specific glycans but do not allow predictable glycoform modulation over a range of values. In this study, we demonstrate the ability to predictably modulate the gly-coform profile of recombinant IgG. Using CRISPR/Cas9, we have engineered nucleotide sugar synthesis pathways in CHO cells expressing recombinant IgG for combinatorial modulation of galactosylation and fucosylation. Knocking out the enzymes UDP-galactose 4 `-epimerase (Gale) and GDP-L-fucose synthase (Fx) resulted in ablation of de novo synthesis of UDP-Gal and GDP-Fuc. With Gale knock-out, the array of N-glycans on recom-binantly expressed IgG is narrowed to agalactosylated glycans, mainly A2F glycan (89%). In the Gale and Fx double knock-out cell line, agalactosylated and afucosylated A2 glycan is predominant (88%). In the double knock-out cell line, galactosylation and fucosylation was entirely dependent on the salvage pathway, which allowed for modulation of UDP-Gal and GDP-Fuc synthesis and intracellular nucleotide sugar availability by controlling the availability of extracellular galactose and fucose. We demonstrate that the glycoform profile of recombinant IgG can be modulated from containing predominantly agalactosylated and afucosylated glycans to up to 42% and 96% galactosylation and fucosylation, respectively, by extracellular feeding of sugars in a dose-dependent manner. By simply varying the availability of extracellular galactose and/or fucose, galactosylation and fucosylation levels can be simultaneously and independently modulated. In addition to achieving the pro-duction of tailored glycoforms, this engineered CHO host platform can cater to the rapid synthesis of variably glycoengineered proteins for evaluation of biological activity.
Keywords: Antibody; Cell engineering; Fucosylation; Fx; Galactosylation; Gale; glycosylation; Nucleotide sugar synthesis; Recombinant therapeutics